Pendampingan UMKM melalui buku kewirausahaan guna mewujudkan wirausahawan desa sepanjang yang produktif dan inovatif - Ahmad Abdullah; Martha Ayu Devitasari; Laili Indah Sari Rohmawati (Universitas Negeri Malang, 2021)
Abstract As an important skill to have, entrepreneurship will bring various benefits for someone who is going to do business or has started a business. However, in the current pandemic situation and conditions, entrepreneurs, especially SMEs, are still experiencing several obstacles. Among these obstacles are limited access to information and insight related to tips for maintaining a business during a pandemic, lack of knowledge about appropriate marketing strategies, and financial management that has not been properly planned. For this reason, the work program initiated by the Throughout Village KKN team aims to aid and share information through written entrepreneurship books so that MSME actors in the Panjang Village can obtain information and understanding related to the business world during the COVID-19 pandemic. The work program was carried out on June 9, 2021, by visiting and distributing entrepreneurship books to several MSME actors in the Panjang Village. The results obtained are that MSME actors in Panjang Village still have their own obstacles in running businesses during the pandemic. Among them are difficulties in adjusting marketing strategies, the number of consumers who are uncertain, difficult to manage business finances, and this of course has an impact on the amount of income that decreases. With the books that were distributed, the MSME players in the Village of Throughout felt helped to increase their information and insight about the business world during the pandemic. Abstrak Sebagai keterampilan yang penting dimiliki, kewirausahaan akan mendatangkan berbagai manfaat bagi seseorang yang akan berbisnis maupun sudah memulai bisnisnya. Namun pada situasi dan kondisi pandemi seperti saat ini, para wirausaha khususnya pelaku UMKM masih mengalami beberapa hambatan. Diantara hambatan tersebut yakni terbatasnya akses terhadap informasi maupun wawasan terkait kiat-kiat mempertahankan usaha di masa pandemi, kurangnya pengetahuan tentang strategi pemasaran yang tepat, dan pengelolaan keuangan yang belum terencana dengan tepat. Untuk itu, program kerja yang digagas oleh tim KKN Desa Sepanjang ini bertujuan untuk melakukan pendampingan serta berbagi informasi melalui buku kewirausahaan yang ditulis sehingga pelaku UMKM di Desa Sepanjang dapat memperoleh informasi dan pemahaman terkait dunia usaha dikala pandemi covid-19. Program kerja dilaksanakan pada tanggal 9 Juni 2021 dengan mendatangi dan membagikan buku kewirausahaan kepada beberapa pelaku UMKM Desa Sepanjang. Hasil yang didapatkan adalah pelaku UMKM di Desa Sepanjang masih memiliki hambatan tersendiri dalam usaha yang dijalankan selama masa pandemi. Diantaranya, kesulitan menyesuaikan strategi pemasaran, jumlah konsumen yang tidak menentu, sulit mengelola keuangan usaha, dan hal ini tentu berimbas pada jumlah pendapatan yang berkurang. Dengan buku yang dibagikan, pelaku UMKM Desa Sepanjang merasa terbantu guna menambah informasi serta wawasan mereka seputar dunia usaha dikala pandemi.